Design and syntheses of GM(3)- and lactose-containing multivalent glycoconjugates. - Park, William Keun Chan. (University of Ottawa (Canada), 1995)
Cell-surface carbohydrates are known to be responsible for various cellular activities. These carbohydrates are involved in many recognition and adhesion processes acting as receptors for viruses, bacteria, toxins, hormones and other cells. The carbohydrates are present on the cell surface in branched forms and are conjugated with proteins and lipids which are embedded in the plasma membrane. Isolation and purification of glycoconjugates from natural sources are difficult to achieve. Thus, syntheses of chemically well-characterized, carbohydrate hapten-containing compounds are called for. In order to achieve this goal, the recently found concept of multivalency is used as a part of synthetic strategy. A ganglioside, GM$\sb3$ has been chosen as a carbohydrate hapten in syntheses of various glycoforms, and lactose has been used as a model-system for the GM$\sb3$. Both carbohydrate haptens have been modified to glycosyl azide forms so that a versatile N-acrylamido function could be provided by facile reduction and acryloylation. The GM$\sb3$ carbohydrate moiety has been constructed by coupling a lactosyl azide derivative as glycosyl acceptor and a thiophenyl sialoside as glycosyl donor in the presence of NIS/TfOH as promotor. Lactose- and GM$\sb3$-containing glycopolymers with different spacer arms and varied lengths have been synthesized. Double immunodiffusions of the GM$\sb3$-containing glycopolymers have been performed for evaluation of their binding interactions with WGA. A single-step reaction to provide a series of lactose-containing telomers has been examined as a facile route to glycoconjugate syntheses. Monomeric N-acrylamidolactose has been telomerized with t-butylmercaptan as telogen in the presence of AIBN as initiator. Similarly, the lactose-containing monomer with hexanoate spacer arm has been telomerized. A dimer was prepared by tethering two lactose-containing monomers with 1,3-propanedithiol. Both the telomers and the tethered dimer have been compared for their inhibitory potencies using a serological assay, enzyme-linked lectin assay (ELLA). All telomers exihibited similar inhibitory potency to that of the free lactose, while the tethered dimer showed the highest inhibition against lactose-containing polymer among the compounds tested. In order to mimic the dendritic nature of cell-surface carbohydrates, synthetic dendrimers using gallic acid as a seeding molecule have been prepared. The dendrimers have been constituted of a 3$\rm\sp{n}$ increase in valency where n represents the n$\rm\sp{th}$ generation. The second generation dendrimer has been assembled using carbodiimide chemistry by coupling the parent amino-ester with the azido-acid daughter molecules. Using chemoselective de-S-acetylation by hydrazinium acetate, thioacetates of lactose derivatives were transformed into the corresponding thiols. The thiols have been conjugated to the electrophilic peripheries of the first and second generation dendrimers. Similarly, the thiols of lactose and lactosamine derivatives have been anchored to already available L-lysine-core dendrimers. These lactose-containing dendrimers have been evaluated for their bindings with the plant lectin Arachis Hypogaea (peanut lectin). The second generation gallic acid-based dendrimer showed strong precipitin band formation with the lectin whereas the first generation dendrimer did not form precipitin band.
Keywords: Biology, Cell.